Technological catch-up and innovative entrepreneurship in Vietnamese firms - Claudio Petti; Minh Nguyen Dang Tuan; Nham Phong Tuan; Mai Pham Thi; Thao Ta Huong; Vishnu Varthan Perumal (Administrative Sciences, 2021)
The article analyses the dynamics of technological catch-up through entrepreneurship in latecomer firms to emerging markets. With this aim, the article introduces Vietnam's experience and illustrates the result of three case studies of Vietnamese technology firms at different stages of their evolution. Insights from the cases reveal all follow an incremental innovation model based on business model 'soft' innovations, mainly in customer-facing activities and partnering, as well as limited products and technology adaptation to local market needs. Consistently with latecomer firms' theory, the market drives these firm's innovation efforts, which are concentrated on developing new services and comprehensive solutions rather than new technologies. Comparisons of the findings with recent and similar experiences of Chinese firms highlight that different stages of catch-up lead to different innovation practices in nature and degree, and the need to strengthen institutions to face competition, rather than use the former to shelter from the latter. The Vietnamese firms' innovation practices and catch-up patterns found are then discussed under the perspective of reaping the benefits of international knowledge and technology flows and the specific challenges faced by Vietnam. The paper concludes with several reflections, lessons learned and perspectives for other newly industrializing emerging countries.
Keywords: 350; catch-up; entrepreneurship; latecomer firms; tech-based firms; Vietnam